CAD based simulation of ball end mill manufacturing. Issue 1 (2nd January 2017) - Baburaj, M.; Ghosh, A.; Shunmugam, M. S.
ABSTRACT: Geometry of micro ball end mill is quite complex, as helical cutting edges are formed on a hemispherical surface. The edge must have proper rake and clearance faces for effective cutting and appropriate radius to strengthen it. Manufacturers of micro tools do not reveal the details, as they are proprietary in nature. In the present work, a CAD approach is proposed to simulate the generation machining of micro ball end mill using appropriate kinematic relations. Different geometries of micro ball end mill can be generated by the approach proposed in the present work. A critical study of virtual micro ball end mills will be useful to understand their performance. The study allows visualization of the cutting angles and edge radius along different transverse sections, as these geometrical parameters influence mechanics of micro cutting. GRAPHICAL ABSTRACT: